Bacterial Community Structure, Diversity, and Fertility of Soil with and without Press Mud in Two Sites in Panay, Philippines: Post pesticide survival of mushrooms and termites in cocoa - Joswa Billonid; Philip Ian Padilla; May Flor Muege; Marilyn Sumayo; Jane Geduspan (Journal of Tropical Life Science, 2023)
Sugarcane farmers commonly use press mud as organic fertilizer to improve the properties of soil and increase crop production. This study compared the effects of press mud on bacterial community structure, bacterial diversity, and physicochemical parameters of sugar mill soil in two sites, the URC Passi Sugar Central and Passi Sugar Central, Inc. both in Panay, Philippines. DNA and soil analyses were conducted to characterize the soil samples with and without press mud from both sites. The results showed that all nutrient contents increased in both areas after press mud application, except in URC Passi Sugar Central, where no increase in phosphorus and sulfur was observed. Bacterial diversity did not significantly increase six months after press mud application. Community pattern results showed that if soil samples within sites were compared, soil with press mud was significantly higher compared to the soil without press mud in terms of OTU richness (Capiz sugar central: 46.00±1.00, 40.00±1.50, respectively; URC Passi Sugar Central: 48.00±0.50, 45.00±0.00, respectively) and carrying capacity (Capiz sugar central: 169±7.36, 125±9.48, respectively; URC Passi Sugar Central: 181±3.80, 162±0.00, respectively) (p<0.05). The same trend was observed in soil samples between sites that were compared. Soil without press mud from URC Passi Sugar Central had a significantly higher compared with soil without press mud of Capiz Sugar Central in terms of OTU richness (45.00±0.00, 40.00±1.50, respectively) and carrying capacity (162±0.00, 125±9.48, respectively) (p<0.05). However, no significant difference was observed in soil with press mud between the two sites in OTU richness, carrying capacity, Shannon, and Evenness analyses (p>0.05). The phylogenetic tree analysis showed that Massilia sp. is closely related to Burkholderia arboris, and Lysobacter sp. is closely related to both Massilia sp.and B. arboris. Generally, press mud application helps increase the available nutrients, diversity, and community patterns in soil, making it good organic fertilizer.